Las políticas ambientales en el Ecuador y sus concordancias con el Art. 414 de la Constitución - Santillán Salazar, Nicole Priscilla (2021)
The purpose of this research work is to carry out a development and analysis of the regulations related to Environmental Law in Ecuador, in addition to analyzing its analogies with International Law and the comparison with the legislation of other Latin American countries. This work analyzes the environmental policies issued and carried out by the Ecuadorian State, in turn, which have contributed effectively to the protection and remediation of the destruction that the environment has suffered, as well as the coercive legislation that is applied in these cases......